Synthesis and Structural Study of a Circular Trimetallic Cu(I) Helicate - Zagal-Moya, J; Zagal-Moya, J; Costamagna-Martra, J; Costamagna-Martra, J; Guerrero-Nunez, J; Guerrero-Nunez, J; Lemus-Chavez, L; Lemus-Chavez, L (INT UNION CRYSTALLOGRAPHY, 2011)
Sin Resumen Disponible